1994
DOI: 10.1126/science.7910981
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ABA Response Gene ABI1 : Features of a Calcium-Modulated Protein Phosphatase

Abstract: The Arabidopsis ABI1 locus is essential for a wide spectrum of abscisic acid (ABA) responses throughout plant development. Here, ABI1 was shown to regulate stomatal aperture in leaves and mitotic activity in root meristems. The ABI1 gene was cloned and predicted to encode a signaling protein. Although its carboxyl-terminal domain is related to serine-threonine phosphatase 2C, the ABI1 protein has a unique amino-terminal extension containing an EF hand calcium-binding site. These results suggest that the ABI1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
569
0
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 761 publications
(584 citation statements)
references
References 36 publications
8
569
0
7
Order By: Relevance
“…In comparison with wild-type a general decrease of basic AtP5CS1 mRNA levels was observed in of ornithine to P5C occurs preferentially under normal conditions, whereas the conversion of glutamate to P5C the abi1-1 mutant, also in the absence of salt induction. In contrast, the axr2 mutation did not affect the basic AtP5CS1 is dominant under stress (Rhodes et al, 1986), the expression and activity of P5CS was proposed to directly mRNA levels, but reduced the induction of AtP5CS1 mRNA accumulation during salt treatment. A similar effect of control the accumulation of proline in response to salinity and dehydration (Delauney and Verma, 1993).…”
Section: Nacl-induced P5cs Mrna Accumulation In Arabidopsismentioning
confidence: 81%
“…In comparison with wild-type a general decrease of basic AtP5CS1 mRNA levels was observed in of ornithine to P5C occurs preferentially under normal conditions, whereas the conversion of glutamate to P5C the abi1-1 mutant, also in the absence of salt induction. In contrast, the axr2 mutation did not affect the basic AtP5CS1 is dominant under stress (Rhodes et al, 1986), the expression and activity of P5CS was proposed to directly mRNA levels, but reduced the induction of AtP5CS1 mRNA accumulation during salt treatment. A similar effect of control the accumulation of proline in response to salinity and dehydration (Delauney and Verma, 1993).…”
Section: Nacl-induced P5cs Mrna Accumulation In Arabidopsismentioning
confidence: 81%
“…Subsequently 2-DE, in conjunction with immunoblotting, revealed that the heterogeneity of cruciferin isoforms far exceeded that predicted from the limited number of expressed genes and mRNA variants described above (Figure 3). The PP2C encoded by ABI1 has been implicated in the regulation of kinase signalling during seed development [29,30], and the abi1-1 mutant is known to exhibit pleiotropic effects. However, specific ABI1 targets have not yet been identified [33].…”
Section: Resultsmentioning
confidence: 99%
“…The ABI1 locus encodes a unique type of protein phosphatase in that the C-terminal domain possesses serine/ threonine protein phosphatase activity similar to that of PP2Cs (class 2C phosphatases), whereas the N-terminal domain contains a calcium-binding EF-hand motif that generally occurs only in the heterodimeric PP2B-type serine/threonine phosphatases. A single point mutation in the abi1-1 mutant significantly reduces PP2C activity [29,30], and genome-wide gene expression profiling indicates that ABA gene regulation is impaired [45]. Although recombinant fusion proteins containing either the whole ABI1 protein or only the phosphatase domain display in vitro phosphatase activity towards 32 P-labelled casein [46,47]; the in vivo targets have not yet been identified.…”
Section: Is Cruciferin An In Vivo Target For the Abi1 Protein Phosphamentioning
confidence: 99%
See 1 more Smart Citation
“…These mutations were isolated 25-years ago by genetic screenings in Arabidopsis, aimed to the identification of ABAinsensitive mutants [27] and the cloning of the mutant loci provided pioneering insights into ABA signaling [28,29,30,31]. Both abi1-1D and abi2-1D are strong ABA-insensitive mutants that show diminished response to ABA in seeds and vegetative tissues, however, analysis of lossof-function alleles indicates that ABI1 and ABI2 gene products, as well as other clade A PP2Cs, are negative regulators of ABA signaling [32,33,34,35].…”
Section: Abi1-1 G180d Abi2-1 G168d and Hab1 G246d Hypermorphic Enzymesmentioning
confidence: 99%